National identity exploration attenuates the identification–prejudice link. (June 2022) - Spiegler, Olivia; Christ, Oliver; Verkuyten, Maykel
Social identity exploration is a process whereby individuals actively seek information about their group membership and show efforts to understand its meaning. Developmental theory argues that exploration-based ingroup commitment is the basis for outgroup positivity. We tested this notion in relation to national identity and attitudes towards immigrants. The results of five experimental studies among German adolescents and early adults ( N = 1, 146; 16–25 years) and one internal meta-analysis suggest that the positive identification–prejudice link is weaker when participants are instructed to explore the meaning of their identity (Study 1). This is not mediated via self-uncertainty (Study 2), but via a reduction in intergroup threat (Study 3) and an increase in deprovincialization (Study 4). In addition, identity exploration enabled strong identifiers to oppose descriptive ingroup norms (Study 5). We conclude that identity exploration can contribute to a further understanding of the identification–prejudice link.